What Went Wrong? A Five-School Review of Master's Theses Reference List. Issue 4 (2nd October 2018) - Yap, Joseph Marmol; Groen, Carlene; Kamilova, Yelizaveta; Terzi, Paschalia; Zvonareva, Darya
ABSTRACT: A good citation and referencing practice starts when a student correctly cites and follows the specified citation format. Academic integrity is closely associated with plagiarism but there is another particular error that academics neglect to verify: the proper formatting of a reference list based on a particular citation style. The purpose of the study is to trace, review and analyze the reference list of selected master's theses submitted to one of the leading universities in Kazakhstan. Results showed a high number of referencing errors. Having a standard format will prevent future mistakes.